Partisipasi Masyarakat Dalam Mewujudkan Kepastian Pelayanan Publik Di Desa Melalui Standar Pelayanan - Rahmat Akbar (Social and Political Science Faculty - Universitas Tidar, 2019)
AbstractAs a democratic country, public participation in implementing governance is a must. Law No. 25/2009 about public service is prepared by open, participative, and progressive which it puts public participation as one of the elements in public service. Public involvement started from drafting phase to an enactment which realized on the instrument of public service standards. Drafting a service standard based on the participatory citizen is one of the service provider’s obligation in order to realize certainty in service. Service standard can prevent maladministration action as well as being a public control. This has been further published in the technical regulations. In reality, however, there are service providers have not arranged the instrument of service standard yet. As one of service delivery, the village is obliged to provide excellent public service. The purpose of this writting to know the consistency of legal arrangements with the practice in the field. This article uses normative legal research methods. Legal rules become references in this paper. A theory which is used to analyze is ‘new public service’ that play citizen as a party in service so that involvement becomes an important element.Key words : Citizen Participation; Public Service; Service Standard